Learning clinical reasoning - Kassirer, Jerome P., 1932-; Wong, John B.; Kopelman, Richard I. (Baltimore, MD : Lippincott Williams & Wilkins Health, 2010)
This resource explains the chief components of the clinical reasoning process, including a discussion of cognitive errors. It contains 69 case studies in which clinicians 'think out loud' about diagnostic and therapeutic dilemmas, and the authors critique these clinicians' reasoning.
Diagnostic hypothesis generation -- Refinement of diagnostic hypotheses -- Use and interpretation of diagnostic tests -- Causal reasoning -- Diagnostic verification -- Therapeutic decision making -- Examining evidence -- Cognitive errors -- Some cognitive concepts -- Learning clinical problem solving -- Introduction to the cases -- Diagnostic hypothesis generation -- Refinement of diagnostic hypotheses -- Use and interpretation of diagnostic tests -- Causal reasoning -- Diagnostic verification -- Therapeutic decision making -- Examining evidence -- Cognitive errors -- Some cognitive concepts -- Learning clinical problem solving.
Includes bibliographical references and index.
Keywords: MEDICAL LOGIC; MEDICAL LOGIC -- CASE STUDIES; DIAGNOSIS; CLINICAL MEDICINE -- DECISION MAKING; DECISION MAKING; CLINICAL MEDICINE